2016
DOI: 10.1038/srep23188
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocytes in Young Infants With Congenital Heart Disease: a Three-Month Window of Proliferation

Abstract: Perinatal reduction in cardiomyocyte cell cycle activity is well established in animal models and humans. However, cardiomyocyte cell cycle activity in infants with congenital heart disease (CHD) is unknown, and may provide important information to improve treatment. Human right atrial specimens were obtained from infants during routine surgery to repair ventricular septal defects. The specimens were divided into three groups: group A (age 1–3 months); group B (age, 4–6 months); and group C (age 7–12 months). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The percentage of Ki67-positive non-cardiomyocytes in each group was 0.39 ± 0.06, 0.17 ± 0.04, and 0.11 ± 0.02, respectively ( p < 0.05; Fig 4). These results indicated that both cardiomyocyte and non-cardiomyocyte proliferation activities were decreased with age, which is consistent with previous reports [6,16]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The percentage of Ki67-positive non-cardiomyocytes in each group was 0.39 ± 0.06, 0.17 ± 0.04, and 0.11 ± 0.02, respectively ( p < 0.05; Fig 4). These results indicated that both cardiomyocyte and non-cardiomyocyte proliferation activities were decreased with age, which is consistent with previous reports [6,16]. …”
Section: Resultssupporting
confidence: 93%
“…Although human cardiomyocytes are more tolerant to reactive oxygen species and may have greater oxidative repair capacity [25], the loss of cell cycling activity is similar to mouse cardiomyocytes [6, 16], which could be due to two possible explanations: 1) Oxidative DNA damage after birth causes permanent cell cycle arrest and subsequent recovery cannot reverse this process, and 2) Oxidative DNA damage only contributes to one component of cell cycle arrest. At birth, under increased hemodynamic stress, neonatal cardiomyocytes undergo cytoskeletal architecture reorganization in order to adjust to postnatal physical stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, this occurs during the first post-natal week 1 , coinciding with their loss of proliferative and regenerative capacity. A similar process occurs in the human heart, although with uncertain timing after birth 12,13 . Notably, a small subpopula-tion of MNDCMs persists in the adult mammalian heart.…”
mentioning
confidence: 76%
“…The recognition that differentiated cardiomyocytes can re-acquire robust proliferative ability during heart regeneration in both zebrafish and mice (Jopling et al, 2010; Porrello et al, 2011; Poss et al, 2002) and that mammalian cardiomyocytes may retain some proliferative capacity during pre-adolescence (Ali et al, 2014; Haubner et al, 2016; Mollova et al, 2013; Naqvi et al, 2014; Polizzotti et al, 2015; Ye et al, 2016) has focused efforts to recapitulate these mechanisms for injury repair, notably for congestive heart failure. The role of Kdm6b histone demethylases in developmentally timed cardiomyocyte (but not cardiac progenitor) proliferation suggests the reversal of epigenetic H3K27me3 silencing marks may be an essential aspect of innate heart regeneration and a promising path to augment therapeutically delivered cardiomyocytes for heart disease.…”
Section: Discussionmentioning
confidence: 99%